Vulnerable Groups: Employment Challenges - Neverauskienė, Laima Okunevičiūtė Okunevičiūtė; Moskvina, Julija (Socialinė teorija, empirija, politika ir praktika, 2014)
Summary The review of the research on labour market groups at risk covers research conducted in the period between 2004 and 2010. It includes applied research carried out at the request of public authorities or other concerned authorities, as well as doctoral dissertations. Mostly, the research focused on such labour market groups at risk as disabled persons, youth and elderly people. The review revealed that special research on the situation of groups at risk in the labour market is a valuable source of information, since there is a lack of information on the national level. A further analysis of issues related to the integration of labour market groups at risk and instruments for reintegration of these groups into labour market would be of great importance. Keywords: labour market groups at risk, disabled people, youth, elderly people.